Comparing the Diagnosis of White Matter Injury in Premature Newborns with Serial MR Imaging and Transfontanel Ultrasonography Findings - Miller, Steven P.; Cozzio, Camilla Ceppi; Goldstein, Ruth B.; Ferriero, Donna M.; Partridge, J. Colin; Vigneron, Daniel B.; Barkovich, A. James (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: The accurate identification of white matter injury in premature neonates is important for counseling parents and for targeting these high risk neonates for appropriate rehabilitation services. The objective of this study was to compare the diagnosis of white matter injury detected by serial MR imaging and ultrasonography of a contemporary cohort of premature neonates.METHODS: Each of the 32 consecutively enrolled neonates was studied with MR imaging at a median postconceptional age of 31.9 weeks (range, 27.6–38.1 weeks) and again at a median postconceptional age of 36.5 weeks (range, 33.4–42.9 weeks) and with serial ultrasonography according to a clinical protocol. Because periventricular echogenicity shown on ultrasonograms evolves over time, both the highest grade of echogenicity and the grade of echogenicity shown on the last neonatal ultrasonogram were used in the analysis to determine the predictive values and correlation (Spearman’s rho) of ultrasonography for predicting white matter abnormalities shown on MR images.RESULTS: White matter abnormalities were diagnosed in 18 (56%) neonates based on MR imaging, consisting of foci of scattered T1 hyperintensity in the periventricular white matter, and in 22 (69%) neonates based on ultrasonography, consisting of abnormal periventricular echogenicity. The severity of white matter abnormalities shown by MR imaging was not correlated with the highest grade of white matter abnormalities detected with ultrasonography (rho=0.18, P=.3) or with the grade of white matter abnormalities shown on the last ultrasonogram (rho = 0.16, P=.4).CONCLUSION: Although ultrasonography is commonly used to screen premature neonates for white matter injury, it was not a sensitive predictor of the milder spectrum of MR imaging-defined white matter abnormalities.